Sesame Street. Kids' favorite country songs [videorecording (DVD)]. - Brooks, Garth; Womack, Lee Ann; Krauss, Alison, 1971- (Sesame Street (Sesame Workshop : Videorecordings), 2007)
Features musical performances from artists such as Garth Brooks, Lee Ann Womack, Allison Krauss, and more. Includes musical segments from Sesame Street episodes and a sing-along karaoke feature.